A new fossil Silis Charpentier, 1825 from Baltic amber (Cantharidae, Silinae, Silini) - Fanti, Fabrizio; Pankowski, Maximilian G. (Zootaxa, 2022)
A new fossil species of the family Cantharidae from Eocene Baltic amber, Silis (Silis) boninoi sp. nov., is described, diagnosed and illustrated. The new species is characterized by its extremely small body size along with a very wide and transverse pronotum with two short and quite robust lobes on each side. It is compared with other known taxa of the genus Silis from Baltic, Dominican and Mexican ambers.